Characterization of the Role of eIF4G in Stimulating Cap- and IRES-Dependent Translation in Aplysia Neurons - Dyer, John (Public Library of Science, 2013)
The rate-limiting step(s) of translation in the nervous system have not been clearly identified. We have been examining this question in the cell body of the Aplysia sensory neuron, where translational regulation is important for the regulation of synaptic strength. In the present study, we examined the role of the adaptor protein eIF4G. We cloned Aplysia eIF4G (Ap4G) and Ap4G contains all the standard metazoan eIF4G protein–protein interaction domains. Overexpressing Ap4G in Aplysia sensory neurons caused an increase in both cap-dependent and internal ribosome entry site (IRES)-dependent translation using a previously characterized bicistronic fluorescent reporter. Unexpectedly, measurement of overall translation using the methionine analog, L-azidohomoalanine, revealed that overexpression of Ap4G did not lead to an increase in overall translation rates. Indeed, the effect of Ap4G on the bicistronic reporter depended on the presence of an upstream open reading frame (uORF) in the 5’ UTR encoded by the vector. We have previously shown that Mnk strongly decreased cap-dependent translation and this depended on a putative 4G binding domain. Here we extend these results showing that even in the absence of the uORF, overexpression of Mnk strongly decreases cap-dependent translation and this depends on the Mnk binding site in eIF4G. Similarly, an increase in cap-dependent translation seen with overexpression of elongation factor 2 kinase did not depend on the uORF. Overall, we show that eIF4G is rate limiting for translation of an mRNA encoding an uORF, but is not generally a rate-limiting step for translation.